Determinants of non-medically indicated cesarean deliveries in Burkina Faso. Issue 1 (November 2016) - Kaboré, Charles; Ridde, Valéry; Kouanda, Seni; Agier, Isabelle; Queuille, Ludovic; Dumont, Alexandre
Abstract: Objective: To identify the factors associated with non-medically indicated cesarean deliveries (NMIC) in Burkina Faso in centers where user fees for cesarean delivery were partially removed. Methods: We carried out a criteria-based audit in 22 referral hospitals, using data from a 6-month prospective observational study, to assess the proportion of NMIC. Multivariate logistic regression analyses were used to identify factors associated with NMIC. Results: The decision of cesarean delivery was not medically indicated in 24% of cases. The factors independently associated with NMIC were urban residence (adjusted OR 1.55; 95% CI, 1.12–2.12; P =0.006), spouse's occupation other than breeder or farmer (aOR varying from 1.77 [95% CI, 1.19–2.62] to 2.15 [95% CI, 1.38–3.32] according to the profession), and cesarean decided by a general practitioner (aOR 1.61; 95% CI, 1.13–2.30; P =0.009). Conclusion: The high percentage of unnecessary cesarean deliveries is in contrast to the unmet needs of women who still deliver outside health facilities. NMIC is associated with both socioeconomic determinants and medical factors. Hence, interventions are needed to improve the skills of healthcare professionals and awareness of women concerning the risks associated with unnecessary cesarean delivery.